Clinical characteristics and treatment outcome in 65 cases with refractory cytopenia of childhood defined according to the WHO 2008 classification. (4th June 2014) - Hasegawa, Daisuke; Chen, Xiaojuan; Hirabayashi, Shinsuke; Ishida, Yasushi; Watanabe, Shizuka; Zaike, Yuji; Tsuchida, Masahiro; Masunaga, Atsuko; Yoshimi, Ayami; Hama, Asahito; Kojima, Seiji; Ito, Masafumi; et al.
Summary This study analysed 65 children who were prospectively registered between 1999 and 2008 and fulfilled the World Health Organization 2008 criteria of refractory cytopenia of childhood (RCC). First‐line therapy was determined by the treating physicians: 25 patients received immunosuppressive therapy (IST), 12 patients received haematopoietic stem cell transplantation (HSCT) and one patient received intensive chemotherapy. The remaining 27 patients were followed without treatment for more than 2 years (watch and wait; WW). In the WW group, 18 patients had stable disease without further intervention. Thirteen of 29 patients (45%) who ended up receiving IST showed response. The combination of ciclosporin and antithymocyte globulin was not shown to be superior to ciclosporin alone with regard to response rate or survival. Of 28 patients who ended up undergoing HSCT, 17 patients are alive in complete remission, whereas nine patients died mostly due to transplantation‐related mortality. The 5‐year overall survival for all patients was 82 ± 5%. Eight patients suffered from disease progression. Patients with monosomy 7 or multilineage‐dysplasia had a significantly higher incidence of disease progression. This analysis revealed heterogeneity in the clinical course of RCC, varying from those who remained stable for long periods to those who progressed to advanced disease.